2005
DOI: 10.1016/j.ememar.2005.09.004
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of skewness and skewness persistence in three emerging markets

Abstract: This paper reports an investigation into the extent and persistence of skewness in stock returns in three emerging markets, namely The Czech Republic, Kenya and Poland. Thee study is undertaken using the extended skew normal distribution and an asymmetric version of the generalised error distribution. The motivation for this paper is the hypothesis that skewness is a particular feature of returns in emerging markets; it may lack persistence and may decline in absolute terms as time passes and the market mature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
0
10
0
2
Order By: Relevance
“…Bekaert et al (1998) is concerned specifically with emerging markets. The data set used here was selected as it is employed in Adcock and Shutes (2005). In this paper it is reported that there is evidence to support the view that skewness in the Czech market was persistent for the period covered in that study.…”
Section: Parameter Estimationmentioning
confidence: 83%
“…Bekaert et al (1998) is concerned specifically with emerging markets. The data set used here was selected as it is employed in Adcock and Shutes (2005). In this paper it is reported that there is evidence to support the view that skewness in the Czech market was persistent for the period covered in that study.…”
Section: Parameter Estimationmentioning
confidence: 83%
“…Adcock and Shutes (2005) find that the skew-normal distribution provides better descriptions of stock returns in the Czech Republic, Kenya, and Poland than the normal distribution. Harvey, Liechty, Lietchy, and Muller (2004) apply the Bayesian approach to skew-normal distribution to determine the optimal portfolio within a family of linear utility functions.…”
Section: Lienmentioning
confidence: 95%
“…Ragunathan and Mitchell [12], analizan la correlación entre las rentabilidades del mercado de acciones como base para Vassal [14] empleó el método Monte Carlo para mostrar que el riesgo en acciones de baja rentabilidad puede ser minimizado manteniendo posiciones en múltiples portafolios de acciones que poseen asimetría positiva. Por su parte, Adcock y Shetes [15], encontraron asimetría en mercados emergentes y que manteniendo más acciones en un portafolio de inversión podría mejorar las probabilidades de mitigar el riesgo asociado con la inversión.…”
Section: Antecedentesunclassified